JOB RESOURCES, WORK ENGAGEMENT, AND HOTEL EMPLOYEE OUTCOMES: A TIME-LAGGED ANALYSIS (vol 25, pg 1127, 2012) - Karatepe, Osman M. (Routledge Journals, Taylor & Francis Ltd, 2012)
This study develops and tests a research model that investigates work engagement as a mediator of the effects of coworker and supervisor support on career satisfaction, service recovery performance, job performance, and creative performance. Data were obtained from frontline hotel employees with a time lag of one month and their immediate supervisors in Cameroon. The relationships were tested using LISREL 8.30 through structural equation modeling. The results demonstrated a better fit for the fully mediated model when compared to the partially mediated model. The results further revealed that work engagement fully mediated the effects of coworker and supervisor support on the previously mentioned outcomes. Implications of the results and their future research directions are offered.
Keywords: Cameroon; Hotel employees; Job outcomes; Job resources; Work engagement